(untitled) (Scientific journal of the Fergana State University, 2024)
Aqueous extracts of plants produced colored extracts. The colored extracts were evaporated, dried, and the IR spectrum of the resulting dry powder was studied. Also observed in the IR spectrum are bending vibrations (NH2) and stretching vibrations of the carbonyl group (CO). The literature was compared and analyzed.